Study on preparation of radiation-crosslinked hydrogel of CMS/PVP/KC/MMT by electron beam irradiation - Nguyen , Thanh Duoc; Doan , Binh; Pham , Thi Thu Hong; Nguyen , Anh Tuan (Nuclear Science and Technology, 2014)
Hydrogel of carboxymethyl starch (CMS)/polyvinyl pyrrolidone (PVP)/kappa – carrageenan (KC)/montmorillonite (MMT) was prepared by electron beam (EB) crosslinking irradiation on an EB linear accelerator UERL-10-15S2 (10 MeV, 15 kW, Russia). The crosslinking capacity of the resulting hydrogels was determined based on gel content and degree of swelling. The mechanical properties, adhesion force on the PE surface and water vapor transmission rate (WVTR) were measured. The preliminary results suggested that the mixture hydrogels (CMS/PVP/KC/MMT) can be used for personal care applications such as facial mask, moisturizing membrane for skin and so on